Uso de gonadotropina coriônica equina associada ao protocolo indutor de ovulação em vacas Zebu em anestro pós-parto - Henrique Moreira Souza (2011)
This experiment was done to study the effect of the diameter of dominant follicle (DF) at the beginning of progesterone protocol, associated or not to equine chorionic gonadotropin (eCG), on follicular growth, ovulation and pregnancy rates of postpartum anestrous Zebu cows. The study was done in three different farms: farm 1 (P1; n=179) - cows with DF 10mm and no eCG at beginning and end of breeding season; farm 2 (P2; n=102) and 3 (P3; n=111) used three treatments: T1=DF<11mm without eCG ; T2=DF<11mm with eCG ; and T3=DF11mm without eCG . Ultrasound evaluations were performed on day 0 and day 8 of progesterone protocol, and at artificial insemination (AI) to measure the diameter of dominant follicle, at day 10 and 21 after AI to detect presence and maintenance of corpus luteum, and day 30 to pregnancy diagnosis. In farm P1, estrous detection and pregnancy rates ranged from 63.3% to 73.3% and 25.5% to 57.9%, respectively. Ovulation and pregnancy rates did not differ (P>0.05) between treatments on farm P2, on average 81.4% and 41.9%, respectively. On farm P3, the follicular growth, ovulation and pregnancy rates were, on average, 0.7±0.5mm/day, 65.8% and 36.0%, and results from treatment T1 were lower (P<0.05) than T2 and T3, but follicular growth rate did not differ from T3. In farm 3 the nutritional management was defficient and used unrestricted suckling, thed eCG increased follicular growth and bigger (P<0.05) corpus luteum, increased ovulation and pregnancy rate in cows presenting DF<11mm. In conclusion, eCG injection is dispensable in protocols used for cows under good nutrition and under restricted suckling.